Sensitivity of Rapid Diagnostic Test and Microscopy in Malaria Diagnosis in Iva-Valley Suburb, Enugu - Chinemelum Joyce, Nwosu; Chinyelu, Ekwunife; Elaine Adaku, Nkwocha (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
Malaria disease is still of public health importance. For effective management and control, an alternative parasite-based diagnosis is paramount. This study focused on determining the sensitivity of rapid diagnostic tests and microscopy in malaria diagnosis in Iva-valley suburb, Enugu State, Nigeria. A total of 379 blood samples were collected from five communities and examined for malaria parasites using microscopy and rapid diagnostic test. Out of the 379 blood samples, 166 (43.80%) were positive for malaria parasites using the CareStart test kit, while 169 (44.6%) were positive using microscopy. Using microscopy as the gold standard, the sensitivity and specificity of the CareStart RDT were 89% and 92.86% respectively, while the positive and negative predictive values were 90.96% and 91.55% respectively. Females had the highest prevalence (69.2 %,) while males had the least (30.8%). However, the difference in gender prevalence was not significant (X2 calc = 1.939, X2 tab=3.841, P>0.05). The age group 11-15 years had the highest prevalence (27.8%), while the 21-25 years age group had the least prevalence (1.18%). This study showed that the accuracy of CareStart RDT is comparable to the gold standard microscopy, making it a suitable diagnostic tool for any local health staff in remote endemic areas.